Continuous participation in a day-care prevention service improves the mobility of the community-dwelling elderly - Yamada, Takayoshi; Demura, Shinichi (International Journal of Health, 2014)
This study aimed to examine the effect of continuous participation in a day-care fall prevention service on the mobility of the community-dwelling elderly. Peak and mean transfer velocities of the center of gravity (PV and MV, respectively) as well as 10-m maximum walking speed (MWS) were calculated for 57 elderly who participated continuously in a day-care fall prevention service, held 24 times every year for 3 years, between 2010 and 2012 [continuous group (CON), age: 76.0 ± 6.1 years], and 157 elderly who participated in it for only the first year within the same period [dropout group (DO), age: 76.6 ± 6.1 years]. No significant difference was found between PV, MV, and MWS in the first year for the CON and DO (t > 1.27, p < 0.05). The, PV and MV of the CON increased significantly within a year (F = 28.1 and 30.5, p < 0.05 in both). Moreover, PV, MV, and MWS of the CON in the third year were significantly higher than those in the DO (t > 2.55, p < 0.05). Our results suggest that continuous participation in a day-care fall prevention service contributes to an improvement in the mobility of community-dwelling elderly individuals. Keywords: Continuity, Nursing Care Prevention Service, Mobility.